2019
DOI: 10.1111/bjd.18560
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological factors associated with death from thin (≤ 1·00 mm) melanoma

Abstract: Summary Background Thin cutaneous melanomas (≤ 1·00 mm) are increasing worldwide, causing around a quarter of all melanoma deaths in the U.S.A. and Australia. Identification of predictive factors for potentially fatal thin melanomas could allow better use of resources for follow‐up. Objectives To identify the clinicopathological factors associated with fatal thin melanomas. Methods This large, nested case–case study extracted data from the population‐based Queensland Cancer Registry, Australia. Our cohort cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…The 8th edition of the AJCC staging manual stated an increased risk of fatality in patients with a melanoma thickness of 0.8-1.0 mm [31]. Claeson et al reported that the risk of fatality in thin melanoma on the scalp was sixfold higher than that on the back [32]. As thin malignant melanomas accounted for a large number of melanomas in our study and scalp location is a risk factor, we explored the cutoff for thin HNM with X-tile, which revealed a thickness of 0.6 mm (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The 8th edition of the AJCC staging manual stated an increased risk of fatality in patients with a melanoma thickness of 0.8-1.0 mm [31]. Claeson et al reported that the risk of fatality in thin melanoma on the scalp was sixfold higher than that on the back [32]. As thin malignant melanomas accounted for a large number of melanomas in our study and scalp location is a risk factor, we explored the cutoff for thin HNM with X-tile, which revealed a thickness of 0.6 mm (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cancers of the skin are a major and growing disease burden among Caucasian populations. The primary driver of melanoma mortality is the thickness of the tumour at diagnosis; therefore, early detection of thin melanomas can optimize outcomes 1–3 . Diagnosing keratinocyte cancers at an early stage reduces the cost of surgical resection and rates of hospital admission 4 …”
Section: Introductionmentioning
confidence: 99%
“…They are usually thicker and have a higher risk for brain metastasis and poorer prognosis, when compared with other body sites or other head and neck melanomas 1–8 . Scalp location has also been recently proved to be a strong prognostic factor of death from thin (≤1.0 mm) melanoma 9 . The factors contributing to the worse prognosis and pathogenesis of scalp melanomas are not yet completely understood 1 …”
Section: Introductionmentioning
confidence: 99%